2022
DOI: 10.1177/21925682221139816
|View full text |Cite
|
Sign up to set email alerts
|

What Preoperative Factors Are Associated With Achieving a Clinically Meaningful Improvement and Satisfaction After Single-Level Transforaminal Lumbar Interbody Fusion for Degenerative Spondylolisthesis?

Abstract: Study design Prospective cohort study. Objectives The purpose of this study was to identify preoperative factors associated with clinically meaningful improvement, patient satisfaction and expectation fulfilment at 2 years follow-up in patients undergoing single-level TLIF for degenerative spondylolisthesis. Methods Patients who underwent a primary, single-level TLIF for degenerative spondylolisthesis between 2006 and 2015 were identified from a prospectively maintained institutional spine registry. Baseline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In contrast, a prior study found that patients with better mental health were more likely to experience superior improvements in pain levels as identified via VAS pain scores after lumbar spine surgery [ 24 ]. Likewise, another study also reported evidence that patients with higher a MCS were more likely to achieve MCID in postoperative PROMs related to disability and surgical satisfaction [ 33 ]. These studies did not utilize the VR-12 questionnaire and had varied follow-up times, which could be possible explanations for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a prior study found that patients with better mental health were more likely to experience superior improvements in pain levels as identified via VAS pain scores after lumbar spine surgery [ 24 ]. Likewise, another study also reported evidence that patients with higher a MCS were more likely to achieve MCID in postoperative PROMs related to disability and surgical satisfaction [ 33 ]. These studies did not utilize the VR-12 questionnaire and had varied follow-up times, which could be possible explanations for these differences.…”
Section: Discussionmentioning
confidence: 99%